TEACHING VOCABULARY AS AN IMPORTANT WAY OF LEARNING LANGUAGE - Shahzoda Shavkatjonova; Shakhlo Khalilova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The learning of vocabulary is an important part in foreign language learning. Vocabulary is considered as central in language teaching and is of paramount importance to a language learner. Teaching vocabulary can be deemed as problematic, as some teachers are not really sure about the best practice in the teaching and sometimes not really aware how to start forming an instructional emphasis on the vocabulary learning. Here was written about the effective teaching vocabulary in English lessons, importance of structural method to teach vocabulary.